Efficacy, safety and economy of denosumab and zoledronic acid in the treatment of bone metastases of solid tumors and multiple myeloma: a systematic review and meta-analysis - Zhong, Li; Chen, Wei; Zheng, Da; Cao, Yuening; Zhu, Ling; Zhu, Zefeng; Liao, Luqin; Dai, Lilin; Wang, Xiaotao; Zeng, Zheng (Frontiers in Oncology, 2026)
ObjectiveTo conduct a comprehensive comparison of the efficacy, safety, and cost-effectiveness of denosumab versus zoledronic acid in patients with bone metastases from solid tumors and multiple myeloma.MethodsA systematic search of PubMed, Web of Science, Embase, and major Chinese databases was performed for studies published up to 30 September 2025. Eligible evidence included randomized controlled trials, cohort studies, and pharmacoeconomic analyses. Random-effects models were applied for quantitative synthesis. The certainty of evidence for key outcomes was assessed using the GRADE framework.ResultsTwenty-one studies were included. Moderate-certainty evidence indicates that denosumab likely delays the time to first skeletal-related event (SRE) (HR = 0.85, 95% CI: 0.79–0.93) and time to first and subsequent SREs (HR = 0.86, 95% CI: 0.76–0.97) relative to zoledronic acid. Subgroup analyses demonstrated that this benefit is pronounced in solid tumors but not observed in multiple myeloma. For survival outcomes, moderate-certainty evidence suggests little to no difference in overall survival (HR = 0.97, P = 0.49) or progression-free survival (HR = 0.99, P = 0.86). Low-certainty evidence suggests that denosumab may reduce the risk of any adverse events (OR = 0.70, P = 0.04) and nephrotoxicity (OR = 0.65, P = 0.02). Pharmacoeconomic evaluations revealed marked geographic heterogeneity: denosumab was generally cost-effective in high-income settings with higher willingness-to-pay thresholds, whereas in resource-limited regions, zoledronic acid remained the more economically favorable option.ConclusionDenosumab probably confers superior protection against SREs in patients with solid tumors and demonstrates a potentially improved renal safety profile compared with zoledronic acid. However, its cost-effectiveness varies substantially across healthcare systems and is strongly shaped by regional pricing structures and willingness-to-pay thresholds. Clinical adoption should therefore consider tumor biology, safety characteristics, and local economic capacity. Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251020691.